Planning in the Management of BUMDes Karya Unggul in Punggul Gedangan Village, Sidoarjo - Utomo, Bagio (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2019)
BUMDes (Village-Owned Enterprises) are formed by the community and for the community, planning in their management already has a vision, mission, goals and work programs but there are still obstacles, namely lack of organization and lack of movement, direction in the management of BUMDes Karya Unggul Desa Punggul, if seen from the management indicators, namely planning or planning in the management of BUMDes in Punggul Village already has a vision, mission, objectives, work program, organizational structure, just how to execute the programs that have been prepared properly. If viewed from the planning indicators or planning has planned to make BUMDes according to or guided by the AD / ART that has been set by the BUMDes Punggul village, it already has a multiplicity of planning like its goals and work programs and has formed business units that will be run which It is hoped that it will be able to help the economy of the Punggul Village community and be able to increase village income. As for the AD / ART data in the form of BUMDes programs, such as savings and loan businesses, market businesses and stationery businesses. This study used a qualitative descriptive method with data collection techniques carried out by means of observation, documentation, interviews with informant determination techniques, data analysis techniques using the theory of Miles and Huberman (1984).